Control Prosody using Multi-Agent System - Matsui, Kenji; Kimura, Kenta; Pérez, Alberto (Advances in distributed computing and artificial intelligence journal, 2014)
Persons who have undergone a laryngectomy have a few options to partially restore speech but no completely satisfactory device. Even though the use of an electrolarynx (EL) is the easiest way for a patient to produce speech, it does not produce a natural tone and appearance is far from normal. Because of that and the fact that none of them are hands-free, the feasibility of using a motion sensor to replace a conventional EL user interface has been explored. A mobile device motion sensor with multi-agent platform has been used to investigate on/off and pitch frequency control capability. A very small battery operated ARM-based control unit has also been developed to evaluate the motion sensor based user-interface. This control unit is placed on the wrist and the vibration device against the throat using support bandage. Two different conversion methods were used for the forearm tilt angle to pitch frequency conversion: linear mapping method and F0 template-based method A perceptual evaluation has been performed with two well-trained normal speakers and ten subjects. The results of the evaluation study showed that both methods are able to produce better speech quality in terms of the naturalness.